Hacking For Dummies
Hacking for dummies / by Kevin Beaver ; foreword by Stuart McClure.This book explore the malicious hacker's mindset, help the reader develop an ethical hacking plan, and cover typical hack attacks and how to counteract them. It will also take the reader through reporting vulnerabilities to upper management, managing security changes, automating the ethical hacking process, and training end users not to be victims of social engineering. This book is fully updated for Windows XP SP2 and Vista, recent rootkits and DoS exploits, Google hacks, and new hacker tools, more